Investigation of the Effects of the Fenoxaprop-p-Ethyl Herbicide and Salicylic Acid on the Ascorbic Acid and Vitamin B6 Vitamers in Wheat Leaves - Yaman, Mustafa; Nalbantoglu, Barbaros (SPRINGER, 2020)
Herbicides inhibit plant growth and development by various mechanisms, and oxidative stress is a common plant response to herbicide treatment. In a limited number of studies, it has been shown that vitamins are also strong antioxidants. It has been also known that salicylic acid (SA), a natural compound, plays a role in the activation of plant defences. This study examined the effects of the fenoxaprop-p-ethyl (FE) herbicide and SA on the ascorbic acid and B-6 vitamers (pyridoxine, pyridoxal, and pyridoxamine) in wheat leaves. After the wheat plants were grown for 15 days, the leaves were subjected to FE, SA (0.05, 0.5 and 5 mM), and FE + SA treatments for 24, 48, and 72 h. Then, the leaves were cut, and levels of ascorbic acid and B-6 vitamers were analyzed. The vitamin analyses were performed by means of HPLC. It was found that the FE has caused to increase the ascorbic acid level but generally to decrease in all three forms of vitamin B-6. When FE and SA treatments are applied together, it has been revealed that SA regulates the increasing of ascorbic acid levels and the decreasing of B-6 vitamers levels by bringing the control levels. It can be concluded that exogenous SA by its contribution on endogenous SA content could play an ameliorating role on herbicide tolerance and the negative effects of herbicides can be reduced on the crop condition by applying an appropriate exogenous SA concentration.
Keywords: Herbicide; Oxidative stress; Vitamin; Salicylic acid; Wheat; ACETYL-COA CARBOXYLASE; FREEZING TOLERANCE; BIOSYNTHESIS; STRESS; RESISTANCE; GENES; ACCUMULATION; INHIBITION; PYRIDOXINE; TOXICITY; Plant Sciences